Les ‘mots en bl-’ du lexique anglais : étude de la structuration des données dans une optique lexico-cognitive - Line Argoud (Lexis: Journal in English Lexicology)
In this paper, I explore the class of English lexical items beginning with bl-. My objective is twofold: firstly, I present the hypothesis that the phonological invariance of this heuristically-formed class corresponds to a notional invariance within two important subsets of ‘bl- words’. I claim that this notional invariance may be traced back to mental representations whose underlying source is the schema (Lakoff & Johnson). Secondly, I consider the part played by aspect in the data provided by the entries for ‘bl- words’ in two dictionaries, the Oxford English Dictionary and the English Dialect Dictionary.